Multiple histidines in the periplasmic domain of the Salmonella enterica sensor kinase SsrA enhance signaling in response to extracellular acidification. Issue 4 (16th January 2015) - Mulder, David T.; McPhee, Joseph B.; Reid‐Yu, Sarah A.; Stogios, Peter J.; Savchenko, Alexei; Coombes, Brian K.
Summary The two‐component regulatory system SsrA‐SsrB in Salmonella enterica controls expression of a virulence gene program required for intracellular survival in host cells. SsrA signaling is induced within the acidic host vacuole in which the bacteria reside; however, the mechanism by which SsrA senses this intracellular environment is unknown. Here, we show that the periplasmic sensor domain of SsrA is enriched in histidine residues that increase SsrA signaling below external pH of 6. While no single histidine accounted for the full acid‐responsiveness of SsrA, we localized the acid‐responsiveness principally to five histidines in the C‐terminal end of the periplasmic sensor domain, with input from additional histidines in the N‐terminal end of the senor. A sensor mutant lacking critical pH‐responsive histidines was defective for acid‐promoted activity, yet retained basal activity similar to wild type at neutral pH, indicating that the role of these histidines is to enhance signaling in response to acidification. In support of this, a pH‐blind mutant was insensitive to the vacuole acidification blocking activity of bafilomycin, and was attenuated for competitive fitness during infection of mice. Our data demonstrate that SsrA contains a histidine‐rich periplasmic sensor that enhances signaling in response to the innate host defense of vacuolar acidification.